Electromyographic inter-limb asymmetry in bench press exercise in elite paralympics weightlifters - Aedo-Muñoz, E.; Sanchez-Ramirez, C.; Moya-Jofre, C.; Bustamante-Garrido, A.; Araya-Ibacache, M.; Dal Bello, F.; Brito, C.-J.; Miarka, B. (ISBS Proceedings Archive (Michigan), 2019)
The purpose of this study was to describe inter-limb asymmetry in three muscle groups in a sample of Paralympic weightlifters during an 80% RM bench press. The sample was composed of 7 subjects belonging to the Chilean elite powerlifting. Surface electromyography was assessed in major pectoral, deltoid anterior and triceps brachii. The magnitude of the response was calculated through root mean square (RMS). Symmetry Index was calculated for an interlimb differences measure. Only the pectoralis major muscle showed significant differences between limbs (right 84.7 ± 41.3; left 66.1 ± 19.3 RMS) (p=0.05) and the SI median greatest value (19.74 ± 24.59%). Anterior deltoid showed high individual differences in two athletes with upper 80% SI values. More studies should assess asymmetry with the objective to decrease this injuries risk factor.